The The Effects of Additioning Purple Sweet Potato Flour (Ipomoea batatas L.) on The Characteristics of White Dragon Fruit Pudding (Selenicereus undatus) - Mujianto, Mujianto; Lili Zalizar; Damat Damat; Rahayu Relawati; Muhammad Dusturuddin Robbany; Nico Syahputra Sebayang; Effendi Andoko (CV. Media Digital Publikasi Indonesia, 2024)
Pudding is one of the processed foods made by mixing agar powder into water, milk, fruit pulp, to vegetable pulp which can produce a gel and has a soft texture. White dragon fruit is a type of fruit that is rarely used as pudding, because it has a less attractive color after being processed. In this research, white dragon fruit pudding by adding purple sweet potato flour to increase the attractiveness of color, enrich the antioxidant activity, and increase the fiber content contained in the pudding to obtain a pudding of functional value. This study used a simple randomized design group (RAK), with a focus factor concentration of purple sweet potato flour consisting of 6 levels, including P0 (0% purple sweet potato flour), P1 (5% purple sweet potato flour), P2 (10% purple sweet potato flour), P3 (15% purple sweet potato flour), P4 (20% purple sweet potato flour), and P5 (25% purple sweet potato flour) with 4 times repetitions. The raw material analysis of purple sweet potato flour includes water content, ash content, fat content, fiber content, and antioxidant activity. Analysis of white dragon fruit pudding products includes analysis of water content, ash content, fat content, fiber content, antioxidant activity, color intensity, texture, and organoleptic test (texture, taste, aroma, color, and preference). The addition of purple sweet potato flour significantly affected the water content, ash content, antioxidant activity, color intensity, texture, and organoleptic test of white dragon fruit pudding. P1 formulation (5% purple sweet potato flour) was the best formulation with the water content of 76.41%, ash content of 0.28%, fat content of 3.56%, fiber content of 0.89%, antioxidant activity of 14.33%, brightness level of 39.35, redness level of 8.02, yellowish level of 3.92, and texture of 0.34 N. Organoleptic test results texture 5 (somewhat chewy), taste 3 (somewhat tasteless purple yam), aroma 2 (not scented purple yam), color 6 (attractive), and preference 6 (like).